Synthesis of Boron Nitride Nanotubes by Self-Propagation High-Temperature Synthesis and Annealing Method. (18th January 2011) - Wang, Jilin; Gu, Yunle; Zhang, Laiping; Zhao, Guowei; Zhang, Zhanhui
Abstract : High-quality boron nitride nanotubes were synthesized by annealing porous precursor in flowing NH3 gas at 1150 ° C. The porous precursor B18 Ca2 (MgO)9 was produced by self-propagation high-temperature synthesis (SHS) method using Mg, B2 O3, and CaB6 as the starting materials, which played an important role in synthesis of BN nanotubes in large quantities. Samples were characterized by SEM, TEM, EDX, HRTEM, X-ray powder diffraction (XRD), Raman, and Fourier transform infrared (FTIR) spectroscopy. The as-synthesized BN nanotubes have an average diameter of about 150 nm with a wall/diameter ratio of 2/3. Mean length of the BN nanotubes was more than 10  μ m. The effects of temperature, time, and the possible mechanism of the growth of the BN nanotubes were also discussed.